Amending mine tailing cover with compost and biochar: effects on vegetation establishment and metal bioaccumulation in the Finnish subarctic - Hagner, Marleena; Uusitalo, Marja; Ruhanen, Hanna; Heiskanen, Juha; Peltola, Rainer; Tiilikkala, Kari; Hyvönen, Juha; Sarala, Pertti; Mäkitalo, Kari (Environmental Science and Pollution Research, 2021)
Abstract In the northern boreal zone, revegetation and landscaping of closed mine tailings are challenging due to the high concentrations of potentially toxic elements; the use of nutrient-poor, glacigenic cover material (till); cool temperatures; and short growing period. Recycled waste materials such as biochar (BC) and composted sewage sludge (CSS) have been suggested to improve soil forming process and revegetation success as well as decrease metal bioavailability in closed mine tailing areas. We conducted two field experiments in old iron mine tailings at Rautuvaara, northern Finland, where the native mine soil or transported cover till soil had not supported plant growth since the mining ended in 1989. The impacts of CSS and spruce ( Picea abies )–derived BC application to till soil on the survival and growth of selected plant species ( Pinus sylvestris , Salix myrsinifolia , and grass mixture containing Festuca rubra , Lolium perenne , and Trifolium repens ) were investigated during two growing seasons. In addition, the potential of BC to reduce bioaccumulation of metals in plants was studied. We found that (1) organic amendment like CSS markedly enhanced the plant growth and is therefore needed for vegetation establishment in tailing sites that contained only transported till cover, and (2) BC application to till soil-CSS mixture further facilitated the success of grass mixtures resulting in 71–250% higher plant biomass. On the other hand, (3) no effects on P. sylvestris or S. myrsinifolia were recorded during the first growing seasons, and (4) accumulation of metals in cover plants was negligible and BC application to till further decreased the accumulation of Al, Cr, and Fe in the plant tissues. Graphical abstract